Development and deployment of genotype-specific LAMP assays for monitoring Pepino mosaic virus (PepMV) in tomato - Warman, Bethan (2017)
Tomato (Solanum lycopersicum) is regarded as one of the most important vegetable crops worldwide, being cultivated across the globe with a total yield of approximately 162 million tonnes in 2012. Pepino mosaic virus (PepMV) is currently the most threatening pathogen to global commercial tomato production. The Potex-virus was first identified on pepino plants in Peru in 1974. PepMV was initially discovered in Europe in 1999 on greenhouse tomato plants in the Netherlands and has since spread worldwide. The virus induces a wide range of symptoms in tomato plants including leaf mosaics, yellow rectangular leaf spots, leaf necrosis, fruit marbling and fruit flaming. The fruit symptoms exhibited by PepMV-infected crops often lead to reductions in the marketability of the fruit. PepMV infection can also be symptomless, making disease diagnosis difficult. Currently, six PepMV genotypes have been characterised; the European (EU) strain, the original Peruvian (LP) isolates, the North American (US1/CH1) strain, the Chilean-2 (CH2) strain and the PES strain recently discovered in wild tomatoes in Peru. The CH2 genotype is the dominant genotype found in PepMV-infected tomato crops in Europe. Mixed-infections with multiple PepMV genotypes can also be observed. Mixed-genotype PepMV infections often induce more severe disease symptoms. PepMV is highly contagious, being spread easily via mechanical means, and is able to survive on glasshouse surfaces, tools, hands and clothes. This means that the hands-on practices required for tomato crop production can result in the rapid dissemination of the virus around the glasshouse environment and to other glasshouses to infect other crops. It is essential that tomato growers are able to identify PepMV infection in their crops to allow for the implementation of strict hygiene protocols to prevent the spread of PepMV to uninfected crops. Loop-mediated isothermal amplification (LAMP) can be used for plant pathogen detection. This study aimed to validate genotype-specific RT-LAMP primers designed by Ling et al. (2013) for the detection of the CH2, EU and US1 genotypes of PepMV. After successful validation, the primers were used to test tomato leaf and fruit samples collected from six crops from four UK tomato sites in order to determine the distribution and occurrence of mixed-genotype PepMV infection in the UK. RT-LAMP tests revealed that PepMV infection was widespread in the crops assessed, with PepMV being detected on all sites. The CH2 genotype was found in single infection in over 60% of the samples tested and mixed-genotype infection was detected in approximately 20% of plants assessed. The symptoms observed were variable between the crops and symptomless infection also existed. The second half of this study aimed to identify sources of PepMV inocula within the glasshouse. Firstly, glasshouse surfaces and equipment from three UK sites were swabbed before and after end-of-season glasshouse cleanups. The pre and post-cleanup swabs were tested using RT-LAMP for the presence of PepMV in order to assess the efficacy of end-of-season cleanups at eliminating PepMV. Seventy six %, 86% and 98% of the pre-clean swabs tested positive for PepMV. Twenty %, 44% and 68% still remained PepMV-positive at Sites 1, 2 and 3, respectively, after end-of-season cleanups. Despite positive results for the post-cleanup swabs being obtained with RT-LAMP, sap inoculation studies revealed that the PepMV detected by RT-LAMP was not viable, indicating that the end-of-season cleanups conducted were successful at eliminating viable PepMV. Secondly, the survival of PepMV in composted tomato waste was monitored. A PepMV-infected tomato crop was chipped and subjected to composting. Compost samples were collected at monthly and then weekly intervals over an approximate sixteen week composting period and tested for the presence of PepMV using RT-LAMP. Samples taken from the chipped crop and stored in a 24ᵒC incubator for the duration of the investigation were used as control samples. The control samples were sampled and tested with RT-LAMP at the same time as the compost samples in order to determine the effect of composting on PepMV. The RT-LAMP amplification times were used as an indication of the level of PepMV within the samples. Results showed that the level of PepMV within the samples did decrease over time and the average level of PepMV in the control samples was greater than that in the compost samples. However, the rate of PepMV degradation did not differ significantly between the compost samples and controls, suggesting that PepMV degrades overtime, irrespective of whether or not the virus is subjected to composting. Finally, water samples from three UK tomato nurseries were collected and concentrated, using a method developed at the National Institute of Biology (NIB) Slovenia, in order to allow for the detection of PepMV using RT-LAMP. PepMV was detected in 50% of the water samples collected, showing that the virus can survive and be transported in water/nutrient solutions. Glasshouse irrigation systems may therefore aid the dissemination of PepMV between crops, particularly if the water is recirculated and is used to irrigate multiple glasshouses.